The Power of the Voice - Abitbol, Jean (Plural Publishing, Incorporated, 2018)
The Power of the Voice is a scientific and personal voyage of exploration into the vocal instrument that each of us possesses without necessarily understanding it or knowing the true measure of its power. Enriched with numerous delightful anecdotes, including some about celebrities and politicians, the reader will better understand how the voice can inspire attraction and even repulsion. This fascinating read will be of interest to people who use their voice often, including singers, actors, teachers, comedians, journalists, politicians, etc.